Post-conflict reconstruction : the complexity and challenges of planning and implementing infrastructure projects in Kosovo - Earnest, James (Curtin University, 2011)
Rehabilitation and reconstruction of social and economic infrastructure in a post-conflict environment are complex and long-debated issues in development cooperation. Both in pre-conflict and post-conflict situations, deepening chaos and disorder can be found at the highest social, economic and political levels, and serious development challenges remain insufficiently addressed. After almost a decade of the war in Kosovo, the providers of infrastructure services for the disaster affected, returning communities are faced with multifaceted problems characterised by a fragile society with political, economic and institutional breakdowns.Planning and implementing reconstruction projects in areas that are affected by conflict has proven to be far more challenging than expected, and has often been considered to be a feeble response from practitioners, aid agencies and government. In addition, genuine community-level involvement in post-conflict planning and decision-making for programs are central to any process for empowerment. With the presence of multiple donors and aid organisations, making informed decisions about complex multifaceted solutions, promoting good governance and better allocation of scarce resources are required to achieve a good outcome in a post-war situation. This also entails having a clearer focus and understanding of planning and implementation of post-war reconstruction projects and programs, thereby leading to nation building.The concept of managing post-conflict reconstruction and development projects according to internationally-accepted project management processes is a relatively new and developing field. The current study looked at how the planning and execution of post-conflict reconstruction and development projects in Kosovo could be used to develop a conceptual framework with which to design projects and programs that would be more likely to yield positive outcomes for society. The impetus for the study was to examine the planning and implementation challenges of rebuilding the economic infrastructure projects by agencies capable of supporting a stable society and economy in these complex, peace-building initiatives. In order to structure the complex question of post-conflict reconstruction and development projects in a more systematic way, a conceptual framework for planning and implementing projects was developed to help rebuild communities in post-conflict settings.The use of mixed method approaches was designed to explore and confirm the research questions, as well as help in understanding the phenomena in the social, cultural and governance context within the project development practice of multilateral agencies in Kosovo. Using a detailed case study approach to the interviews and survey data, the study not only identified program strengths and weaknesses of the current project management processes, but also identified the differences of opinion within the project team in project planning and implementation in their wider sense.The findings of the study identified a poor quality of planning and implementation of reconstruction projects in an environment of complexity, change and uncertainty. The interpretation of respondents’ data shows that there remain considerable challenges in Kosovo’s reconstruction of key infrastructure. There is evidence that both aid organisations’ constructed project management processes and international aid agencies practices do not work effectively in a community service delivery setting. However, the study raised some very significant findings for a broader approach to community involvement in project identification, planning and implementation. The study showed that there continue to be differences in project communication, cost, quality, procurement and risk management. Finally, the study’s findings demonstrated that success in post-conflict reconstruction depends on the ability to understand the full complexities of the political environment, as well as the ability to coordinate peace-building operations in an effective manner.